Bibliometric Analysis: Antibiotics Compounds as Persistent Organic Pollutants in Hospital Wastewater - Nisa Nurhidayanti; Neny Mulyani (Universitas Muhammadiyah Yogyakarta, 2023)
Hospitals produce domestic waste containing medicinal micropollutants, which are persistent and harmful to the environment and living things. Conventional wastewater treatment has not been able to remove persistent organic compounds properly. Bibliometric analysis in this study aims to identify antibiotic compounds as persistent organic pollutants in hospital wastewater. This study aims to obtain the results of the characterization of pharmaceutical product compounds as persistent organic pollutants in hospital domestic wastewater. The method used was qualitative descriptive to describe the bibliometric analysis performance by producing a network visualization of the chosen topic. The bibliometric analysis used Publish or Perish software as a search tool for journal metadata and Vosviewer as software to help find research gaps. This article is a bibliometric analysis using Scopus-indexed journals. The development of Scopus indexed international scientific publications on the topic of antibiotics in hospital wastewater during 2010 - 2022 on Scopus totaling 954 articles published in publications with the subject of environmental science, health, science, pharmacy, and engineering, with the most types of publications being in research articles and review article. Of the 10 articles with the highest citations, they could be grouped into 2 types of articles, 7 of which were research articles and 3 were literature articles reviews.